PENGARUH JENIS DAN TEMPERATUR KOAGULAN TERHADAP MORFOLOGI DAN KARAKTERISTIK MEMBRAN SELULOSA ASETAT - Radiman, C. L.; Eka, I. (UI Scholars Hub, 2007)
Effects of type and temperature of coagulant on the morphology and characteristics of cellulose acetate membranes. Cellulose acetate membranes have been made in this work by phase inversion method using 10 wt. % of cellulose acetate, 10 wt. % of formamide and 80 wt. % of acetone. The dope was coagulated in water or 2-propanol at varied temperature ranging between 5 and 25 oC. The characteristics of the obtained membranes were measured by their water flux and rejection towards dextrans with varied molecular mass, while membrane morphology was observed by Scanning Electron Microscope (SEM). The results showed that membranes coagulated in 2-propanol was denser than the ones coagulated in water resulting in higher rejection of dextrans and lower water permeability. Coagulation in lower temperatures decreased the diffusion rate between solvent and non-solvent and the membrane structure was less porous.